Oral Aesthetics and the Power of Symbols in the Plays of Derek Walcott and Bate Besong - Yimbu, Emmanuel (Traektorii͡a︡ nauki : mezhdunarodnyĭ ėlektronnyĭ nauchnyĭ zhurnal, 2016)
Although song and dance are independent art, they are being employed adequately in today’s theatrical production as dramatic elements. This paper examines the relevance of songs as an aspect of oral aesthetics in the plays of Derek Walcott and Bate Besong. It also argues that like any other aspect of drama, Walcott and Besong succeeded in using songs and dances to play the triple roles of informing, educating and entertaining. Furthermore, this paper stresses the importance of symbolism in revealing the playwrights aesthetic ideologies. The playwright’s attribute symbolic meaning or significance to setting, characters, objects, events, actions and relationships with the principal intention of commenting on the deteriorating nature of their various postcolonial societies.Framed on the basis of the New Historicist assumption that, every text of literature reflects both within and without itself. The analyses in this paper, reveal that, in their attempts to conceive an independent national cultural identity, the playwrights use songs and symbolic vocabularies that are recognisably indigenous or at least different from European representations, but yet intelligible within a global grammar of post-war politics. The various songs and symbols that permeate the works under study, play multiple roles and carry various meanings if read within the context of the postcolonial societies they all set out to represent. The playwrights succeeded in crystallising songs and symbols into veritable instruments of conscientisation and revolution.